Assessment of Biofield Energy Healing Based Vitamin D3 Effects on Bone Health Parameters Using Human Osteoblast Cell Line (MG-63) - Kumar Trivedi, Mahendra; Branton, Alice; Trivedi, Dahryn; Nayak, Gopal; Jana, Snehasis (International Journal of Nutrition, 2018)
Poor bone health is the primary health issue, which leads to significant health problems, stress and worsening the patients' quality of life. The potential of The Trivedi Effect®- Biofield Energy Healing on vitamin D3 as a test item (TI) and DMEM on MG-63 cells was investigated. The test items were treated with The Trivedi Effect® by Mahendra Kumar Trivedi and divided as Biofield Energy Treated (BT) and untreated (UT) test items. An increase in ALP activity, collagen levels, and bone mineralization was considered as the biomarker for bone health. MTT data showed that the test samples observed nontoxic in the tested concentrations. The level of ALP was significantly increased by 832.9% and 209.4% in the UT-DMEM+BT-TI and BT-DMEM+UT-TI groups, respectively at 10 µg/mL, while 222.9% increase in the BT-DMEM+BT-TI at 1 µg/mL compared to the untreated group. Collagen was significantly increased by 487.7% and 544.5% in the BT-DMEM+UT-TI and BT-DMEM+BT-TI groups, respectively at 100 µg/mL, while 116.2% at 1 µg/mL in UT-DMEM+BT-TI compared to the untreated group. Moreover, the percent of bone mineralization was significantly increased in the UT-DMEM+BT-TI and BT-DMEM+UT-TI groups by 344.9% and 149.7%, respectively at 50 µg/mL, while 183.6% in the BT-DMEM+BT-TI group at 100 µg/mL compared to the untreated group. Thus, the role of Biofield Energy Treated vitamin D3 and DMEM in order to control osteoblast function and its direct effects on bone mineralization can be used to improve bone disorders.
Keywords: Vitamin D3; Bone Health; Osteoblasts; MG-63 Cell Line; Alkaline Phosphatase; Collagen; Bone Mineralization